The Effect of Financial Distress, Leverage, and Profitability on Audit Report Lag with Firm Size as a Moderating Variable (Case Study on FnB Companies Listed on the IDX in 2020-2023) - Putri Dilla Maliana; Indah Permata Dewi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of financial distress, leverage, and profitability on audit report lag, with firm size as a moderating variable. The research focuses on food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A purposive sampling method was used to select companies that consistently published complete annual financial statements in Indonesian Rupiah during the observation period. Audit report lag is treated as the dependent variable, while financial distress, leverage, and profitability serve as the independent variables. Firm size, measured by the logarithm of total assets, acts as the moderating variable. The data were analyzed using descriptive statistics and Moderated Regression Analysis (MRA). Hypothesis testing was performed through partial t-tests and simultaneous F-tests at a 5% significance level. The results indicate that financial distress and leverage do not significantly affect audit report lag, while profitability has a significant positive impact. These findings confirm only the third hypothesis, suggesting that profitable firms may experience delays in audit completion, possibly due to increased financial complexity.